Investigating Engineered Ribonucleoprotein Particles to Improve Oral RNAi Delivery in Crop Insect Pests - Gillet, François-Xavier; Garcia, Rayssa A.; Macedo, Leonardo L. P.; Albuquerque, Erika V. S.; Silva, Maria C. M.; Grossi-de-Sa, Maria F. (Frontiers in Physiology, 2017)
Genetically modified (GM) crops producing double-stranded RNAs (dsRNAs) are being investigated largely as an RNA interference (RNAi)-based resistance strategy against crop insect pests. However, limitations of this strategy include the sensitivity of dsRNA to insect gut nucleases and its poor insect cell membrane penetration. Working with the insect pest cotton boll weevil (Anthonomus grandis), we showed that the chimeric protein PTD-DRBD (peptide transduction domain - dsRNA binding domain) combined with dsRNA forms a ribonucleoprotein particle (RNP) that improves the effectiveness of the RNAi mechanism in the insect. The RNP slows down nuclease activity, probably by masking the dsRNA. Furthermore, PTD-mediated internalization in insect gut cells is achieved within minutes after plasma membrane contact, limiting the exposure time of the RNPs to gut nucleases. Therefore, the RNP provides an approximately 2-fold increase in the efficiency of insect gene silencing upon oral delivery when compared to naked dsRNA. Taken together, these data demonstrate the role of engineered RNPs in improving dsRNA stability and cellular entry, representing a path toward the design of enhanced RNAi strategies in GM plants against crop insect pests.